Dual effects of 17β-oestradiol on interleukin 1β-induced proteoglycan degradation in chondrocytes. Issue 2 (13th January 2004) - Richette, P; Dumontier, M F; François, M; Tsagris, L; Korwin-Zmijowska, C; Rannou, F; Corvol, M T
Abstract : Objective: To determine whether 17β-oestradiol (E2) modulates interleukin (IL) 1β-induced proteoglycan degradation in chondrocytes, and to analyse the part played by metalloproteinases (MMPs) in this process. Methods: Primary cultured rabbit articular chondrocytes were prepared and treated with 10 ng/ml IL1β combined or not with 0.1–10 nM E2. Neosynthesised proteoglycans (PGs) were evaluated after incorporation of [ 35 SO4 ]sulphate and further analysed after chromatography on a Sepharose 2B column. Chondrocyte mRNA levels of aggrecan, MMP-1, -3, -13, and tissue inhibitor of metalloproteinase-1 (TIMP-1) were studied by northern blot. MMP-1 activity was measured by zymography. MMP-1 gene transcription was studied by transient transfection of chondrocytes with an MMP-1-luciferase construct. Results: E2 modulated the IL1β-induced total sulphated PGs in rabbit articular chondrocytes, which decreased as the E2 concentration was increased. At a low concentration (0.1 nmol/l) E2 counteracts the IL1β-induced decrease in sulphated PG, while at high concentration (10 nmol/l) E2 enhances the IL1β effects. A biphasic E2 effect was also observed on IL1β-induced disaggregation of PG, 53–58 kDa gelatinolytic activity, and MMP-1, -3, and -13 mRNA levels. In contrast, E2 did not modify the level of aggrecan mRNA and had no effect on TIMP-1 mRNA expression. Finally, simultaneous addition of IL1β and E2 (0.1–10 nmol/l) did not modify IL1β-induced MMP-1-luciferase activity, suggesting that E2 effects probably occur at the post-transcriptional level of MMP gene expression. Conclusion: Oestrogen concentration may have an inverse effect on IL1β stimulated proteoglycan degradation and MMP production by chondrocytes.